Uji Efektifitas Sediaan Gel Ekstrak Daun Pegagan (Centella Asiatica ) Formula 10% untuk Penangganan Striae Gravidarum pada Ibu Hamil - Mariana Isir; Vera Iriani Abdullah (Program Studi S1 Kebidanan - Fakultas Sains dan Kesehatan Universitas PGRI Adi Buana Surabaya, 2021)
Referring to the Sustainable Development Goals, there are 4 pillars, which one of them is the realization of biodiversity through bioprospecting activities in the fulfillment of medicinal raw materials. Centella asiatica or daun pegagan is a plant with an aromatic smell and has many benefits. Centella asiatica contains collagen. The collagen has functions to tighten and elasticize the skin fibers so that it can overcome striae gravidarum. The purpose of this study was to analyze the effectiveness of the gel preparation of Centella asiatica. This gel was made by extracting the Centella asiatica leaves at 10% concentration for the treatment of striae gravidarum grade 1, 2 and 3 which examined before and after the intervention. The research method is quasi-experimental with a one group pretest-posttest design approach. The repondents are 3 pregnant women who had experiencing striae gravidarum grade 1, 2 and 3. This research was carried out at the Mariyat Health Center, Sorong Regency from June to August 2021. The research instrument use G.S.S. Atwal L.K (2006) method to assess the degree of striae gravidarum, paired T test for the analysis. The results of the research, gel preparation of Centella asiatica leaves extract formula (10%) is effective for treatment of striae gravidarum grade 1,2 and 3.